PROCEDURAL PRINCIPLES AND PROSPECTS OF REVIEW OF COURT DECISIONS IN COURT ACTIVITY (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the legal nature of the newly introduced judicial review body in the judicial system of the Republic of Uzbekistan, its role and significance in judicial activity. The specific procedural features of supervisory proceedings, as well as the scope of powers of the supervisory bodies at the regional and Supreme Court levels, have been examined. The author has put forward scientific proposals for ensuring the stability of court decisions and improving the mechanism for correcting judicial errors.